Josias Weitbrecht, the founder of syndesmology, and the history of the retinacula of Weitbrecht - Bartoníček, Jan; Naňka, Ondřej (Surgical and radiologic anatomy, 2019)
"Syndesmologia siue historia ligamentorum corporis humani", published in 1742 by a German anatomist Josias Weitbrecht (1702-1747), who for a long time lived and worked in St. Petersburg, is the first comprehensive textbook of syndesmology. The accuracy and quality of the accompanying illustrations are fascinating, even after almost 300 years. Weitbrecht was also the first to describe the synovial folds of the hip joint, later named after him as the retinacula of Weitbrecht. This eponym appeared in the first half of the nineteenth century in the studies of femoral neck fractures published in the UK. In the study of syndesmology, Weitbrecht was followed by a number of outstanding authors of that time, such as Meckel, Barkow, Arnold, Henle, Humphry and Fick.
Keywords: dějiny 19. století; Humans; lékařské ilustrace; Anatomists; Syndesmology; History, 19th Century; Anatomy; Joint Capsule; kloubní pouzdro; Hip Joint; Ligaments; Medical Illustration; lidé; Retinacula of Weitbrecht; Synovial folds of the hip; Textbooks as Topic; Male; anatomie; History, 18th Century; anatomové; dějiny 18. století; ligamenta; učebnice jako téma; Arthrology; mužské pohlaví; kyčelní kloub; Weitbrecht